Incidence of Dental Caries in Relation with Cariogenic food and Socioeconomic Status among Pediatric Patients - Marium Azfar, Sana Adeeba Islam, Batool Sajjad, Nosheen Khawar, Syed Ahmed Omer, Waheed Gul Shaikh, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: One of the most prevalent oral health conditions in children around the world is dental caries, which has painful and distressing effects. The purpose of this study was to investigate the relationship of dental caries and the utilization of cariogenic food among children aged 5 to 10 years old in private and public schools. Study design: The study was conducted in the Department of Community Dentistry, Sindh Institute of Oral Health Sciences, Jinnah Sindh Medical University, Karachi , from June 2022 to December 2022. Methods: The total participants of this study were 150 child both male and female who suffered tooth decay or caries and mouth cavity. The age range was 5 to 10 years. A self-structured questionnaire about eating habits, caries status, socioeconomic status, and an oral cavity assessment was used during the study. The children divided into two groups, private and government school related to the specific areas of food habit. The data was analyzed by SPSS 21 software. Results: Participants had dental caries in 87% of cases. More than 80% of people with low socioeconomic status had multiple caries. In 80% of the participants, who regularly ate the cariogenic food, multiple caries were discovered. Cariogenic foods and tooth decay were found to be significantly correlated, p 0.05. Conclusions: Children under the age of 10 years had a high prevalence of dental caries in the study. Children from lower middle class families were more likely to have dental caries. In patients with a high prevalence of caries, frequent consumption of sweetened beverages and medications as well as a lack of regular use of fluoridated rinses were all positively correlated with an increased number of teeth. These findings imply that in order to increase oral hygienic and awareness of dental care and evaluate on the basis of school child to promote oral health and protection. Keywords: Dental caries, cariogenic food, Tooth decay, Socioenomic status.